Broad bandwidth SOA-based multiwavelength laser incorporating a bidirectional Lyot filter - Sulaiman A.H.; Kadir M.Z.A.; Yusoff N.M.; Cholan N.A.; Abdullah F.; Abas A.F.; Alresheedi M.T.; Mahdi M.A. (Science Press, 2023)
Semiconductor optical amplifiers; Broad bandwidths; Fixed wavelength; Intensity-dependent; Multi-wavelength lasers; Multiwavelength generation; Multiwavelength spectra; Polarization parameters; Power stability; Bandwidth